COPD and asthma: similarities and differences - Barnes, Peter (Henry Stewart Talks, 2021)
Clinical differences between Asthma and COPD, Differences in pathology and cellular mechanisms, Similarities in acute exacerbations, Comorbidities and disease progression, Differences in response to therapy, Overlap in Asthma and COPD, Asthma in smokers, GOLD and GINA